MOVE STRUCTURE OF ABSTRACTS ON ASIAN EFL JOURNAL - Nurhayati nhi (Wanastra: Jurnal Bahasa dan Sastra, 2015)
Genre analysis is a means of studying spoken and written discourse. Genre is also as a structuring device used for scientific writing such as articles of journal. The aim of the present study is to describe move structure of research article abstracts. The move or rhetorical structure model employed as the framework for analysis of the data was Hyland’s.  The sources of data are abstracts of Asian EFL journal articles published between 2005-2009. The number of the article abstracts chosen as the source of the data was fifty. The findings indicated that there were four conventional moves in the abstracts, namely Purpose Move (M2), Method move (M3), Product move (M4), and Conclusion move (M5).   It was found that M2, M3, and M4 occurred in all of the 50 abstracts or 100% while M5 occurred in 38 abstracts or 76%.  Introduction move (M1) was an optional move since it was only 24 abstracts or 48%.  The most frequent move structure appeared in the abstracts was M2-M3-M4-M5 whose total was 23 abstracts or 46%. Finally, the implication of the findings is that the result of the research can be as an empirical reference for novice writers in writing abstracts. Keywords: Genre, Move Structure, Hyland’s